Effect of low dose allopurinol on glycemic control and glycemic variability in patients with type 2 diabetes mellitus: A cross-sectional study - Manal M. Alem (Heliyon, 2022)
Background: Type 2 diabetes mellitus (DM), gout, and asymptomatic hyperuricemia are inter-connected pathologies. Glycemic control (GC), involving a range of treatments is central to the management of DM, whereas allopurinol continues to be the most widely recommended urate lowering agent. Allopurinol has been shown to possess anti-oxidant properties: this study explores the potential effect of allopurinol on glucose homeostasis. Methods: This is an observational study with a cross-sectional design performed on patients with type 2 diabetes mellitus (DM), recruited from centers in Saudi Arabia. Patients were divided into two groups; allopurinol users; (for gout or asymptomatic hyperuricemia) and a matching disease control group. Patient demographics, co-morbid conditions, biochemical tests, and pharmacological treatments were extracted from electronic records to investigate the effect of allopurinol therapy on Glycemic control (GC), as assessed by glycated haemoglobin (HbA1c as primary endpoint), and on parameters of glycaemic variability (GV) (secondary endpoints). Results: A total of 194 patients with type 2 DM were recruited (97 in both groups). The two groups were matched for age, sex, and duration of DM: mean age: 59.4 years, 73% males, and 122 months in the allopurinol group vs 59.6 years, 73% males, and 113 months in the control group. Antidiabetic medications were matched between the two groups. In the allopurinol group, it was prescribed with a daily dose of 100 mg, for 77% of the patients, with median duration of 39.5 months. HbA1c values were; 6.90% (6.20, 7.80) in the allopurinol group vs 7.30% (6.60, 8.40) in the control group (P = 0.010). Parameters of GV were calculated from 3 consecutive fasting blood sugar (FBS) readings: variability independent of the mean (VIM) was 0.140 in the allopurinol group vs 0.987 in the control group (P < 0.001). Conclusion: Concomitant low-dose allopurinol therapy in patients with type 2 DM was associated with modest but significant improvements in GC and GV.